PERANAN LINGKUNGAN KERJA DALAM MENINGKATKAN KEPUASAN KERJA - Juhana , Dudung (Majalah Bisnis & IPTEK, 2021)
The role of human resources at this time a scourge and a central issue because it is a very large assets and priceless (unvaluable assets) as well as determining the company's development in the future. Agencies or institutions always tried to encourage and empower its resources, including human resources, it is intended that this will spur the empowerment resources and provide a positive impact on the development and progress of the institution or institutions concerned. Working environment and job satisfaction are variables that also affect the performance. Keywords: work environment; job satisfaction